Nuclear factor-kappa B p50-induced microRNA-20a-3p plays a detrimental role in sepsis-induced acute kidney injury: NF-κB induced microRNA-20a-3p in AKI - Mao, Weihong; Wang, Xiaoming; Zhang, Yongchen; Zhu, Huding; Dai, Li; Chen, Juanjuan (Cellular and Molecular Biology, 2023)
Sepsis is the most common cause of acute kidney injury (AKI). Based on microarray-based clustering analysis of miRNAs altered in the kidneys of LPS-AKI mice, miR-20a-3p was upregulated in the kidney tissues of lipopolysaccharide (LPS)-treated mice. We aimed to reveal the functions of miR-20a-3p in septic AKI by establishing the LPS-stimulated mouse model of AKI and constructing the LPS-stimulated HK-2 cells. Reverse transcription-quantitative PCR was used to quantify miR-20a-3p expression and inflammation-associated factors including MCP-1, TNF-α, and IL-6. Silencing of miR-20a-3p reduced inflammation and apoptosis in kidneys as well as alleviated AKI symptoms in mice. The LPS-induced inflammatory response and apoptosis in HK-2 cells were rescued by miR-20a-3p silence. Moreover, nuclear factor-kappa B (NF-κB) is a transcriptional factor for miR-20a-3p to increase its expression. The binding of NF-κB p50 and miR-20a-3p promoter was verified by ChIP assay. To sum up, miR-20a-3p is transcriptionally activated by NF-κB p50, playing a harmful role in sepsis-induced AKI by inducing inflammation and apoptosis.